Variations among Italian Isolates of the «Heterobasidion annosum» P Group Detected Using the M13 Minisatellite - Maresi, Giorgio; Petta, Mario; Capretti, Paolo; Tegli, Stefania (Phytopathologia Mediterranea, 2001)
The genetic variability of 22 Italian isolates of Heterobasidion annosum belonging to intersterility group (ISG) P was studied by using the M13 minisatellite, as marker, in PCR experiments. Phylogenetic dendrogram constructed with the UPGMA method clearly differentiated the P group isolates from F and S ones, used for comparison. Within the tested population, P isolates related by the same geographical origin tend to form separated clusters. A stronger differentiation was observed in this Italian P population than in other European P populations previously studied with the same methods. The observed stronger genetic differentiation may be related to a more marked differentiation in host populations, considering that Italy was a refugee area during glaciation and a differentiation centre after. Also the specific morphology of Italy may not allow the genetic flow between the pathogen populations of different areas. Further investigations are needed to relate the genetic differentiation with isolates virulence.